Socialdemokratiets indvandrerpolitik: Opbrud og foreløbigt parlamentarisk slutspil under Svend Aukens formandsperiode (1987-1992) - Vad Jønsson, Heidi (Arbejderhistorie, 2013)
Heidi Vad Jønsson: The Social Democrat’s Integration Policy. Break-up and preliminary parlimentary playoff during Svend Auken’s chairmanship (1987-1992). Arbejderhistorie 2/2013, pp. 22-43. Immigration and integration are two salient themes, which have proven to be highly problematic for the Danish Social Democratic Party. This became evident, when the party lost the general election in 2001 to the Liberals, the Conservatives and the new pro-national, anti-immigration party, Danish People’s Party. One of the main explanations for the loss of power was irresolute and vague political statements, where internal debates and conflicts within the party dominated. The electoral consequences of these intraparty conflicts are clear, but it is, however, not so evident, why immigration and integration were such conflictual themes in the Social Democratic Party. The explanation is to be found within the party: an analysis of the development of an immigrant policy through an intra-party policy development shows that these themes, immigration and integration, gave rise to a multidimensional conflict where both the problem definition, politicization, suggested solutions etc. were different depending on the level of governance (national or local). Even though there were attempts to coin integration as a Social Democratic solution to immigrants’ problems, the conflicts remained present also after the Social Democrats re-entered office in 1993. This article covers the period from 1987, when a new chairman was elected to 1992, where a Social Democratic parliamentary motion on better integration of immigrants was passed in Parliament. The previous period from 1979 to 1987 is covered in a previous article in Arbejdehistorie no 1, 2013.